تقييم أداء آبار ضخ المياه من طبقة المياه الجوفية المضغوطة في بانياس اعتماداً على تجربة مراحل الهبوط والنهوض - شريف بدر حايك (Tishreen University, 2019)
يتضمن البحث دراسة تحليلية لتجارب أداء البئر، اعتماداً على تجربة الهبوط على مراحل والنهوض في بئر ضخ مفردة في بانياس، محفورة في طبقة حاملة لمياه جوفية مضغوطة في توضعات الكريتاسي. تسهم الدراسة التحليلية بتقييم بارامترات فواقد البئر الخطية وغير الخطية ومعامل جدار البئر، وقيمة الناقلية المائية للطبقة الحاملة للمياه الجوفية المضغوطة، إضافةً إلى استنتاج معادلة الهبوط - تصريف للحصول على التصريف الأمثل للبئر، الأمر الذي يمكننا من الإدارة المثلى للموارد المائية الجوفية المتاحة. تسمح تجربة أداء البئر المفردة في بانياس والتي تتميز بسهولة التنفيذ وانخفاض التكاليف، بتحديد غزارة البئر والتي تقدر بـ 600 m3/h مقابل هبوط لايزيد على 6m، وذلك بعد تنفيذ عمليات تطوير جيدة للطبقة الحاملة للمياه الجوفية.     This research contains an analytical study of well performance tests, depending on the experiment of drawdown and recovery stages in a single pumping well in Banias. This well is drilled in a confined aquifer in cretaceous deposits.The analytical study contributes to evaluating the parameters of linear and nonlinear head losses, and calculating the well skin and transmissivity of the aquifer, as well as deducting the equation of the discharge - drawdown to get the optimum discharge of the well, which makes the optimum management of the groundwater resources available. The well performance test in the pumping well of Banias involves simple execution and low costs, and gives us 600 m3/day and drawdown of no more than 6m. But before the test, the aquifer must undergo certain developmental processes.